Bibliometric Analysis of Global Research on Organizational Citizenship Behavior From 2000 to 2019 - Yue Guiling; Siti Aisyah Panatik; Mohammad Saipol Mohd Sukor; Noraini Rusbadrol; Li Cunlin (SAGE Open, 2022)
Over the last two decades, researchers have put significant efforts into exploring knowledge in the area of organizational citizenship behavior (OCB). This study aimed to investigate the global research trends in the OCB field based on publication outputs. The analysis focused on the top authors, journals, institutions, and countries. Using the Scopus database, a total of 4,324 publications from 2000 to 2019 were retrieved. A series of bibliometric indicators such as h-index, citations, and productivity were used to conduct the performance analysis. Moreover, the VOS viewer was employed to visualize the scientific landscapes. The graphical analysis used bibliographic co-authorship coupling among affiliated countries and author keywords from the bibliographic coupling of co-occurrence. The result indicated that there had been a dramatically increasing trend of study on OCB. In addition, the United States ranked first in terms of production, journals, citation impact, co-authorship, institutions, and authors in this subject. Furthermore, OCB has mainly been associated with the topics of job satisfaction and leadership. Apart from that, some other themes linked with OCB in recent studies were also found out. Our research plays an informative and complementary role as it provided most of the key aspects of OCB.